Dignity and Dissent in Humans and Non-humans. - Matthias, Andreas (Science & Engineering Ethics, 2020)
Is there a difference between human beings and those based on artificial intelligence (AI) that would affect their ability to be subjects of (human-like) dignity? This paper first examines the philosophical notion of (human) dignity as Immanuel Kant derives it from the moral autonomy of the individual. It then asks whether animals and AI systems can claim Kantian dignity or whether there is a sharp divide between human beings, animals and AI systems regarding their ability to be subjects of dignity. How this question is answered depends crucially on one's understanding of what constitutes human dignity and autonomy, and what requirements one places upon systems in order for them to be seen as morally autonomous.